2009
DOI: 10.4155/bio.09.134
|View full text |Cite
|
Sign up to set email alerts
|

2009 White Paper on Recent Issues in Regulated Bioanalysis from The 3rd Calibration and Validation Group Workshop

Abstract: The 3rd Calibration and Validation Group Workshop on Recent Issues in Regulated Bioanalysis was organized by the Calibration and Validation Group as a 1.5-day full immersion workshop for contract research organizations, pharmaceutical companies and regulatory agencies to discuss several 'hot' topics concerning bioanalytical issues and regulatory challenges. A consensus was reached among panelists and attendees on many points regarding method validation of small molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 8 publications
0
54
0
Order By: Relevance
“…It was stated at that time, however, that the anticoagulant used in the study protocol should be consistent with the validation, otherwise additional testing should be done [3]. Following 2 years of testing the impact of anticoagulant counterions by industry, it was concluded in 2011 that no significant impact had been observed.…”
Section: Anticoagulant Counterionsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was stated at that time, however, that the anticoagulant used in the study protocol should be consistent with the validation, otherwise additional testing should be done [3]. Following 2 years of testing the impact of anticoagulant counterions by industry, it was concluded in 2011 that no significant impact had been observed.…”
Section: Anticoagulant Counterionsmentioning
confidence: 99%
“…Discussions continued in 2008, where it was confirmed that ISR was being successfully implemented within the industry, although there were still clarifications needed regarding the amount of samples necessary and the final criteria to be used [2]. The following year, consensus stipulated that the number of samples to be re-assayed for the ISR evaluation should be between 5% and 10%, based on the attendees' experiences in LCMS [3]. The recommendation was extended to LBAs in 2010, with the additional statement that the same dilution factor as the original analysis is not required as long as supporting parallelism data exist, but is usually selected in practice [4].…”
Section: Incurred Sample Reanalysismentioning
confidence: 99%
See 3 more Smart Citations